Magnitude and associated factors of intimate partner violence among youth women in Ethiopia: multilevel analysis based on 2016 Ethiopian Demographic and Health Survey - Nuhamin Tesfa Tsega; Daniel Gashaneh Belay; Fantu Mamo Aragaw; Melaku Hunie Asratie; Moges Gashaw; Mastewal Endalew (BMC, 2022)
Abstract Background The period of youth is important for the foundation of healthy and stable relationships, women's health and well-being. Youth women face a higher risk of experiencing violence than older women. Intimate partner violence (IPV) against youth women is a significant public health concern. Despite paramount negative health consequences of IPV for the survivor, as per our knowledge, research study on IPV and associated factors among youth women in Ethiopia is scarce. Therefore, this study aimed to assess the magnitude and associated factors of IPV among youth women in Ethiopia. Methods The data was accessed from 2016 Ethiopia demographic and health survey (EDHS) which was a cross sectional population based household survey. It was also conducted using a multi-stage stratified random cluster sampling approach. The data were cleaned, weighted, and analyzed using STATA Version 14 software. The total weighted sample of 1077 youth women were used in this study. Multilevel logistic regression modeling was used to determine factors associated with IPV among youth women. Adjusted odds ratio (AOR) with 95% confidence interval (CI) and p value < 0.05 were used to declare the significant variables. Results Among the total participants, 30.27% (95% CI 27.59, 33.09) of youth women experienced IPV. Individual level variables such as: Being widowed/divorced/separated (AOR = 2.28; 95% CI 1.33, 3.91), having a partner who drinks alcohol (AOR = 5.76; 95% CI 3.42, 9.69), witnessing inter-parental violence during childhood (AOR = 3.45; 95% CI 2.21, 5.37), being afraid of partners (AOR = 7.09; 95% CI 4.30, 11.68), and from community level variables, youth women residing in communities with a low proportion of educated youth women (AOR = 0.31; 95% CI 0.13, 0.78) were significantly associated with having experience of IPV. Conclusion The magnitude of intimate partner violence among youth women in Ethiopia was relatively high as compared to the global estimate of IPV. Individual and community level variables such as currently widowed/divorced/separated women, having a partner who drinks alcohol, witnessing inter-parental violence, being afraid of partner, and women from a low proportion of community level youth women's education were significantly associated with intimate partner violence. To decrease this public health problem, it is better to strengthen legislation on the purchase and sale of alcohol, provide legal protection for separated/divorced women, establish effective legal response services for IPV, promote gender equality, and provide psychological support for those who witnessed inter-parental violence during childhood to reduce IPV.